2013
DOI: 10.1177/2158244013505855
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in the Identification of Gifted Students With Co-Existing Disabilities

Abstract: Federal law ensures all students with disabilities the right to a Free, Appropriate Public Education (FAPE). However, current policies governing a student’s eligibility for services may contribute to the underidentification of gifted children with co-existing disabilities—the Twice-Exceptional. The emphasis on below-grade-level (or lower) performance, without regard to ability or potential weaknesses, misses twice-exceptional students. Those who perform at grade level, by using advanced conceptual abilities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 9 publications
0
44
0
2
Order By: Relevance
“…Children served under the Individuals with Disabilities Education Act (IDEA) make up 13% of American students (Peters, Gentry, Whiting, & McBee, 2019). Twice exceptional students often have dramatic discrepancies between their strengths and weaknesses (Silverman, 2013), which make their Full Scale IQ (FSIQ) scores uninterpretable (Flanagan & Kaufman, 2004), and often prevent them from being eligible for gifted services (Gilman et al, 2013). The examiner must separate the indicators of giftedness from the symptoms of disability to facilitate placement in gifted programs and acquire services for the child's disabilities.…”
Section: The Critical Role Of School Psychologistsmentioning
confidence: 99%
“…Children served under the Individuals with Disabilities Education Act (IDEA) make up 13% of American students (Peters, Gentry, Whiting, & McBee, 2019). Twice exceptional students often have dramatic discrepancies between their strengths and weaknesses (Silverman, 2013), which make their Full Scale IQ (FSIQ) scores uninterpretable (Flanagan & Kaufman, 2004), and often prevent them from being eligible for gifted services (Gilman et al, 2013). The examiner must separate the indicators of giftedness from the symptoms of disability to facilitate placement in gifted programs and acquire services for the child's disabilities.…”
Section: The Critical Role Of School Psychologistsmentioning
confidence: 99%
“…By examining rates of identified gifted SLD, gifted, and SLD profiles based on various specified identification criteria, she found that solely using a discrepancy model (1.5 SD s) would overidentify gifted SLD, a finding supported by the psychometric holes present in the discrepancy model because of measurement error and regression to the mean (Fletcher, Lyon, Fuchs, & Barnes, 2007). Yet, Maddocks (2018) further noted the importance of discrepancy models in identifying gifted students with learning disabilities (Gilman et al, 2013) because it is the best way to recognize individual areas of talent and disability. For example, a student with a Verbal Comprehension Index score of 135 whose reading scores vary from 95 to 100 may be reading within an “average” level but is certainly not performing academically as one might expect with verbal skills greater than two standard deviations above the mean.…”
Section: Twice‐exceptionality and The School Psychologistmentioning
confidence: 99%
“…Twice exceptional students form a notable group of students in America's schools. Although there has not been any systematic evaluation of the prevalence of 2e, there are some preliminary estimates and a general consensus that 2e students are underidentified (Gilman et al., 2013). Thus, only using intellectual giftedness and learning disabilities as the bases of 2e status, it has been estimated that there are about 360,000–385,000 students who are 2e (National Education Association, 2006).…”
Section: Twice Exceptional and Delinquencymentioning
confidence: 99%
“…Yet, importantly, there is no single definition of 2e status. On the contrary, there is a lot of discussion in the literature with regard to how this status should be defined (Gilman et al., 2013; McCoach, Kehle, Bray, & Siegle, 2001). One working definition has reached substantial consensus, among twenty‐six organizations that support the research and educational needs of 2e students (Baldwin, Baum, Pereles, & Hughes, 2015): “Twice exceptional individuals evidence exceptional ability and disability, which results in a unique set of circumstances.…”
Section: Twice Exceptional and Delinquencymentioning
confidence: 99%